Measurement of the relative B−→D0/D[ast]0/D[astast]0[mu]μ−ν[bar][mu] branching fractions using B- mesons from B[bar][ast]0s2 decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Physical review, 2019)
The decay of the narrow resonance ¯B*0s2→B−K+ can be used to determine the B− momentum in partially reconstructed decays without any assumptions on the decay products of the B− meson. This technique is employed for the first time to distinguish contributions from D0, D*0, and higher-mass charmed states (D**0) in semileptonic B− decays by using the missing-mass distribution. The measurement is performed using a data sample corresponding to an integrated luminosity of 3.0 fb−1 collected with the LHCb detector in pp collisions at center-of-mass energies of 7 and 8 TeV. The resulting branching fractions relative to the inclusive B−→D0Xμ−¯νμ are fD0=B(B−→D0μ−¯νμ)/B(B−→D0Xμ−¯νμ)=0.25±0.06,fD**0=B(B−→(D**0→D0X)μ−¯νμ)/B(B−→D0Xμ−¯νμ)=0.21±0.07, with fD*0=1−fD0−fD**0 making up the remainder.
Im Titel ist [ast] als Tropfensternchen dargestellt
Im Titel sind [ast] sowie "0" und die Minuszeichen hochgestellt, [my] und s2 tiefgestellt
Im Titel ist [mu] als griechischer Buchstabe dargestellt
LHCb Collaboration, R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, M. Neuner, A. Piucci, N. Skidmore, M. Stahl, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 01.10.2019